Provenance of the Chugach-Prince William terrane through U/Pb dating of detrital zircons, Baranof Island, SE Alaska - Rick, Brianna Joy (Carleton Digital Commons, 2014)
The southern Alaska continental margin contains the Chugach-Prince William Terrane (CPW), a ~2200 km Mesozoic-Tertiary accretionary complex composed mainly of deep-water turbidites and is intruded by 62-47 Ma near trench plutons of the Sanak- Baranof Belt (SBB). Location of the CPW during intrusion has been proposed to have occurred either 1) near its current latitude, interacting with the migrating Kula- Ressurection TRT triple junction, or 2) at a southern latitude, interacting with the fixed Kula-Farallon TRT triple junction while migrating northward. This paper presents U/Pb detrital zircon data (n=725) from the Sitka Graywacke and its metamorphic equivalent, the Baranof Schist, on southern Baranof Island in an effort to better understand correlations along strike across the CPW. Maximum depositional ages (MDA) reveal an inboard to outboard (NE to SW) younging progression from ~100 Ma to ~60 Ma, suggesting nearly continuous deposition. The Sitka Graywacke can be packaged into three groups younging inboard to outboard: A) an inboard Albian belt deposited 95-105 Ma, B) an intermediate Campanian-Maastrichtian Belt deposited 65-75 Ma, C) an outboard Paleocene belt deposited 60-65 Ma. U/Pb detrital zircon data show that the youngest and most outboard Paleocene belt (60-65 Ma) on Baranof Island correlates to the Whale Bay belt (60-69 Ma) of the Orca Group in Prince William Sound. Composite detrital zircon data from the Shumigan Islands, Kodiak Island, Seward, Prince William Sound, and Baranof Island reinforce along-strike correlations across the CPW. These sites have a significant 1800-2000 Ma Precambrian grain age population, suggesting a Northern Laurentian signal for the CPW extending to Baranof Island. These data support the restoration of the Yakutat microplate, with a Southern Laurentian signal, south of Baranof Island.